VIRAL WORLD global relations during the covid-19 pandemic. - Bui, Long T. ([S.l.] : ROUTLEDGE, 2024)
This book argues that the catastrophe of COVID-19 provided a momentous time for groups, institutions, and states to reassess their worldviews and relationship to the entire world. Following multiple case studies across dozens of countries throughout the course of the pandemic, this book is a timely contribution to cultural knowledge about the pandemic and the viral politics at the heart of it. Mapping the various forms of global consciousness and connectivity engendered by the crisis, the book offers the framework of "viral worlding," defined as viral forms of relationality, becoming, and communication. It demonstrates how worlding or world-making processes accelerated with the novel coronavirus. New emergent forms of being global "went viral" to address conditions of inequality as well as forge possibilities for societal transformation. Considering the tumult wrought by the pandemic, Bui analyzes progressive movements for democracy, abolition, feminism, environmentalism, and socialism against the world-shattering forces of capitalism, authoritarianism, racism, and militarism. Focusing on ways the pandemic disproportionately impacted marginalized communities, particularly in the Global South, this book juxtaposes the closing of their lifeworlds and social worlds by hegemonic global actors with increased collective demands for freedom, mobility, and justice by vulnerable people. The breadth and depth of the book thus provides students, scholars, and general readers with critical insights to understanding the world(s) of COVID-19 and collective efforts to build better new ones.
Keywords: COVID-19 (Disease); COVID-19 Pandemic, 2020- -- Influence; HEALTH & FITNESS / Diseases / General